Association of functional levels and serum vitamin D among children with cerebral palsy - Yusnita, Afni; Saing, Johannes H.; Hobani, Alhassan H.; Aziz, Abdul; Nasution, Badai B. (Narra X, 2024)
Children with cerebral palsy are more susceptible to deficiency of vitamin D due to less sunlight exposure, poor dietary intake, and long-term use of anti-epileptic drugs, which disrupt their metabolism, resulting in changes in bone mineral density, osteopenia, and rickets. The aim of this study was to investigate the association between gross motor functional levels and vitamin D status in cerebral palsy children. A cross-sectional study was conducted among cerebral palsy patients aged 2–6 years at Haji Adam Malik Hospital, Medan, Indonesia, from November 2022 to April 2023. The levels of the gross motor function classification system (GMFCS) were classified into two groups: ambulatory (GMFCS I, II, III) and non-ambulatory (GMFCS IV, V). Vitamin D status was classified based on serum 25(OH)D levels as normal (30–100 ng/mL), insufficiency (21–29 ng/mL), and deficiency (<20 ng/mL). A total of 85 children with cerebral palsy were included in this study, categorized as ambulatory (n=28, 32.9%) and non-ambulatory (n=57, 67%). The mean serum vitamin D level was 21.92±9.07 ng/L. As many as 54.1% (n=46) of the total children were categorized as vitamin D deficient, followed by insufficient (n=25, 29.4%) and normal vitamin D level (n=14, 16.5%). Age (p=0.310), sex (p=0.590), nutritional status (p=0.269), and types of cerebral palsy (p=0.271) were not associated with vitamin D status. However, there was a significant association between GMFCS levels and circulating vitamin D levels (p<0.001). In a logistic regression model, children classified as ambulatory were more likely to have better vitamin D status, with odds ratios of 12.30 (95%CI: 3.61–41.90) for deficient versus insufficient and 10.93 (95%CI: 2.67–44.69) for deficient versus normal. In conclusion, there was a significant association between functional levels and vitamin D status among children with cerebral palsy.